APPLICATION OF PROBLEM BASED E-LKPD TO STUDENTS’ STATISTICS LEARNING OUTCOMES - Sutamrin, Sutamrin; Rahman, Abdul; Pratiwi, Putri Regina (Universitas Cokroaminoto Palopo, 2025)
This study aims to determine whether the application of problem-based E-LKPD can improve the learning outcomes of statistics of class VIII students of SMPN 1 Libureng. This research is a pre-experimental research with one group pretest-posttest method. The population in this study were all VIII grade SMPN 1 Libureng consisting of 2 classes and the sample of this study was class VIII B as many as 28 students. The research instruments used were pretest and posttest for student learning outcomes before and after the application of problem-based E-LKPD on statistics material. The data generated in this study will be analyzed with a quantitative approach through the application of descriptive statistical methods and inferential statistical analysis. The percentage of implementation of learning activities based on the overall lesson plan is 97% has been implemented. In addition, the average pretest score of students was 39.85 and the posttest score of students was 82.04 from an ideal score of 100. The normalized N-gain score was 0.69 in the moderate category and met the category of completeness in KKM and classically by 85.19%. Meanwhile, student responses obtained an average of 91.07% out of 100% in the very high category. The results of inferential statistical analysis of this study showed that the student learning outcomes test data were normally distributed and homogeneous. The hypothesis test used in this study is the one sample t-test where the 0,000 which indicates is rejected. So that the results of the study can be concluded that there is an increase in student learning outcomes in statistics through the application of problem-based E-LKPD in class VIII B SMP Negeri 1 Libureng.